Perbandingan Penggunaan Lem Bulu Mata dan Eye Cream sebagai Eyeshadow Base pada Tata Rias Mata Pengantin Gaun Panjang - Nurdalyla Nurdalyla; Tyas Asih Surya Mentari (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
This study aims to compare the use of eyelash glue and eye cream as an eyeshadow base in bridal makeup with long gowns, based on evaluation indicators of surface smoothness, color sharpness, durability, and panelist preference. The research employs an experimental method with a one-shot case study design. The sample consisted of 6 people, 3 of whom were given the treatment of using eyelash glue as an eyeshadow base, and 3 were given eye cream as an eyeshadow base. The sampling technique used was purposive random sampling. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing. The results showed no significant difference in surface smoothness using eyelash glue and eye cream as an eyeshadow base with a p-value of 0.336 (p>0.05). There was no significant difference in color sharpness using eyelash glue and eye cream as an eyeshadow base with a p-value of 0.294 (p>0.05). However, there was a significant difference in durability using eyelash glue and eye cream as an eyeshadow base with a p-value of 0.013 (p<0.05). There was no significant difference in panelist preference for using eyelash glue and eye cream as an eyeshadow base with a p-value of 0.051 (p>0.05).For bridal makeup with long gowns, it is recommended to use eyelash glue as an eyeshadow base due to its better durability compared to eye cream, lasting 5-7 hours.